Critical Approaches to the History of Western Herbal Medicine From Classical Antiquity to the Early Modern Period - Francia, Susan; Stobart, Anne (Bloomsbury Academic, 2014)
This open access collection provides historians with a coherent guide to a variety of sources in relation to medicinal plants that they have thus far lacked, grappling with questions such as: Why the history of Western herbal medicine has received such little research coverage in any systematic and authoritative way, even though it has figured large in both lay and learned healthcare of the past? And what methods and sources are most appropriate for the study of medicinal herbs and herbal practices of the past? Critical Approaches to the History of Western Herbal Medicine encourages a serious re-assessment of research in the history of herbal medicine and provides examples of appropriate methodologies and critical examinations of relevant sources. In this innovative collection, historians and researchers from a range of disciplines come together to share material on the identification and use of medicinal plants, the activities of people involved with herbal medicine and the investigation of past herbal therapeutic beliefs and practice. Classical and medieval scholars, social and literary historians, archaeologists and ethnobotanists all contribute to this exploration of the history of Western herbal medicine. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.